Dinamika Produktivitas Padi, Harga Eceran Beras (HEB), dan Harga Pembelian Pemerintah (HPP), serta Korelasi antara HPP dan HEB - Tinjung Mary Prihtanti; Maria Pangestika (Jurnal Ilmu Pertanian Indonesia, 2020)
Rice is the staple food for most of the population of Indonesia. The government set the HPP (government purchasing price) to trigger the increased productivity of rice in the country as well as to improve the welfare/income of farmers. This study aimed to analyze the dynamics of rice productivity, the dynamics of HPP and HEB (retail price of rice), and to analyze the correlation between the productivity of rice, HPP of grain, and HEB in Java in the period of 2010-2014. The analysis showed that in 2010-2014, rice production tended to fluctuate, while the HPP and HEB tended to increase every year, but it is known that there is a correlation between the HPP of grain and HEB in Java. Keywords: productivity, rice, government purchasing price, retail price of rice, Java Island